An Efficient Model for Secure and Scalable Health Log Management in Cloud using EH-ABE - Dhanapal, R.; Visalakshi, P.; G.Parthiban, K. (International Journal of Engineering and Technology, 2018)
Cloud computing is a significant computing archetype from which the resources of the computing framework are afforded as on-demand services over the Internet. Considering the advancements of cloud, so many applications based on Health Log Management (HLM) are being developed. Though this paradigm is promising, it also bears many challenges on security and access control of data when it is shared over cloud server. Applying cryptographic methods is an effective way in order to make the sensitive data more confidential from unauthorized parties. That is, to ensure better access control to patient’s health log shared on cloud, it is vital that the records to be encrypted using an efficient technique before outsourcing. Moreover, while focusing on fine grained access control in shared health log, the main consideration has to be on scalable key management and access flexibility. With those concerns, an efficient model has been proposed in this paper using cryptographically enforced security mechanisms. Enhanced Hierarchical-Attribute Based Encryption (EH-ABE) is the technique used here to encrypt the patient/ data owner’s health log and it effectively helps to obtain secure and scalable access control on the shared health log. As a novel try in secure data storage, multi data owner model has been accomplished here. This scenario classifies the owners in HLM into collective security domains that significantly minimize the complication in key management both in owner and user sides. And the experimental analysis portrays that the affirmed work considerably reduces the computation complexity, memory and time utilization, and also enables security, flexibility and scalability on Health Log Management in an effective manner.